ANALISIS HUBUNGAN PENGETAHUAN DENGAN PERILAKU MASYARAKAT TERHADAP PENCEGAHAN PENULARAN COVID-19 DI KELURAHAN KORONG GADANG - shanti dafris (Akper Kesdam I/Bukit Barisan Padang, 2020)
Coronavirus Disease 2019 or Covid-19 is a pandemic that caused high mortality rates in various parts of the world, including Indonesia. The importance of public awareness to break the chain of transmission of Covid-19. Knowledge about Covid-19 is fundamental, so people can make decisions about behaving appropriately to break the chain of transmission of Covid-19. The research objective was to determine the analysis of people's knowledge and behavior on preventing Covid-19 transmission in Kelurahan Korong Gadang. This research is quantitative. In this research, the sample was 38 residents of the Kelurahan Korong Gadang who were selected using the purposive sampling technique. The results showed that 65.8% of respondents had high knowledge about Covid-19, 68.4% of respondents had good behavior towards preventing the transmission of Covid-19, and there was a relationship between knowledge and behavior towards the prevention of Covid-19 transmission.